2020
DOI: 10.1016/j.imlet.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting, a possible priming tool for host defense against SARS-CoV-2 infection: Crosstalk among calorie restriction, autophagy and immune response

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 81 publications
(102 reference statements)
0
47
0
1
Order By: Relevance
“…IF can activate immune responses ( Cheng et al, 2014 ) and induce autophagy, which is the elimination of dysfunctional organelles and proteins, as well as invading pathogens ( Bagherniya et al, 2018 ), and through distinct mechanisms, stimulates the immune system and primes host defense; therefore, along with the other effects mentioned above, IF could be a potential preventative approach to COVID-19 ( Hannan et al, 2020 ). However, this is not recommended for everyone, as spontaneous fasting could have adverse effects even among healthy individuals.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…IF can activate immune responses ( Cheng et al, 2014 ) and induce autophagy, which is the elimination of dysfunctional organelles and proteins, as well as invading pathogens ( Bagherniya et al, 2018 ), and through distinct mechanisms, stimulates the immune system and primes host defense; therefore, along with the other effects mentioned above, IF could be a potential preventative approach to COVID-19 ( Hannan et al, 2020 ). However, this is not recommended for everyone, as spontaneous fasting could have adverse effects even among healthy individuals.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…SARS-CoV-2 infection suppresses autophagy (Gassen et al, 2020;Hannan, Rahman, et al, 2020). While autophagy machinery is essential for their replication, some viruses evolved strategies to evade autophagy flux (Gassen et al, 2019).…”
Section: Autophagymentioning
confidence: 99%
“…As a proof of concept, recent study demonstrated the utility of three different autophagy-inducing drugs, spermidine, MK02206, and niclosamide, in restricting SARS-CoV-2 propagation [ 138 ]. Autophagy induction and related upregulation of overall immunity helps combat exacerbations and is suggested as an immunity boosting strategy as a preventive measure against COVID-19 [ 139 ]. In addition to boosting immunity, dampening viral load, and allowing SARS-COV2 clearance, autophagy induction may provide strategic advantage in the treatment of COVID-19 and prevention of negative outcomes, which makes it a subject of ongoing studies.…”
Section: Autophagy Dysfunction In Respiratory Diseasesmentioning
confidence: 99%